China's Place in Regional and Global Governance: A New World Comes Into View. Issue 4 (23rd June 2016) - Beeson, Mark; Li, Fujian
Abstract: The 'rise of China' means that – once again – China plays a pivotal role in international affairs. China's economic weight and growing political influence means that its foreign policies and the ideas that shape them have major consequences for established ideas about 'global governance'. Rather than accepting the institutional and ideational status quo, however, Chinese policy makers are actively trying to develop a new international order through the creation of new institutions such as the Asian Infrastructure Investment Bank, and the 'One Belt, One Road' blueprint for international trade and investment centered on China. The paper explains how this process is developing and assesses its implications for the extant international order. Abstract : If observers of the contemporary international system can agree on nothing else they can probably concur that it is in flux. It is not simply the range of challenges and problems that are subsumed under the rubric of global governance that is noteworthy, but the range of actors that are involved—or trying to be involved—in determining political, economic and even strategic outcomes